ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN SUBSEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - , (Politeknik Sawunggalih Aji, 2023)
One way that can show how a company's financial performance is good or not is by analyzing financial statements consisting of liquidity, solvency, activity, and profitability ratios. By obtaining the ratio of liquidity, solvency, activity, and profitability, the company can measure the performance of the company that is being run. The purpose of this research is to determine the results of the analysis of liquidity ratios, solvency, activity, and profitability on the financial performance of Retail Trading Subsector Companies Listed on the Indonesia Stock Exchange (PT. Ramayana Lestari Sentosa Tbk, PT Supra Boga Lestari Tbk, PT. Kokoh Inti Arebama Tbk) in 2016-2019. The results of this study show that the company's liquidity ratio is good, the solvency ratio is quite good, the activity ratio is good, and the company's profitability ratio is good so that the financial performance is stated to be quite good. The conclusion of this study is the financial performance of the Retail Trading Subsector Companies Listed on the Indonesia Stock Exchange at the company PT. Ramayana Lestari Sentosa Tbk, PT Supra Boga Lestari Tbk, PT. Sturdy Inti Arebama Tbk) in 2016-2019 is quite good when viewed from financial ratios. Although the company must focus on managing its debt.